From texts to bodies - Murray, Jacqueline, author. Link
1 online resource.
Keywords: "From Texts to Bodies: Sexes, Genders, and Sexualities in Premodern Europe reflects the historiographical changes to the study of women, gender, and sexuality in premodern Europe across the 1990s into the 2010s. Developing from post-Baby Boom interest in marriage and the family, subsequently inspired by feminist theory and cultural studies, scholars turned their gaze to the wider field of sex and gender. Using an interdisciplinary methodology and a broad cross-section of medieval primary sources, these articles trace the evolution of medieval studies from the family, through women and gender, to focus on sex and sexuality, concluding with critical analyses of men, masculinity, and male embodiment. Part One focuses on medieval women within the context of marriage, family, and the church and reveals new approaches to recovering women's experiences. The articles sit at the transition point between recuperative women's history and critical gender history. Part Two uses an interdisciplinary lens to examine the body, sex, and sexuality and the intersections of sex/sexualities and genders. The innovative articles in Part Three, comprise the foundations for the critical analysis of premodern men, masculinity, embodiment, and male sexuality. Together, these studies demonstrate the expansion of research from the examination of theoretical texts to the analysis of bodies as lived experience. This volume will be of interest to scholars and students of premodern marriage, genders, sexualities, and embodiment, as well as those interested in the social and religious contexts of premodern society. Clear and accessible, this volume also provides an introduction and overview for readers with a broad interest in the Middle Ages"--